The Role of Saudi Animation in Preserving and Reviving Saudi Cultural Identity - Alhumaidi, Afaf (International Journal of Language and Literary Studies, 2025)
Amid the dominance of Western animation—which often imposes idealised beauty norms, rigid gender roles, and orientalist depictions of Arabs—Saudi animation is emerging as a countercultural force reclaiming local narratives. This paper critically examines Ya’rub, a Saudi animated series rooted in mythology and heritage, to analyze how it reconstruct Saudi identity through indigenous storytelling. By drawing on identity theory, postcolonial theory, and feminist critiques of media, this analysis reveals that Ya’rub reframes gender by portraying intellectually and morally empowered female figures, reclaims folklore as a source of national pride, and integrates scientific imagination within culturally grounded framework. These strategies collectively challenge Western hegemonic aesthetics and position Saudi animation as a site of epistemic resistance and creative nation-building. The findings highlight how Ya’rub employs mythic imagination and cultural pedagogy to cultivate self-awareness, reassert cultural authenticity, and promote a multidimensional Arab identity.